Four new infaunal decapod crustaceans (Caridea: Alpheidae and Gebiidea: Axianassidae) from Lizard Island, Australia, one of them also occurring in Moorea, French Polynesia - Anker, Arthur (Zootaxa, 2011)
Four new species of marine infaunal decapod crustaceans are described from Lizard Island, Great Barrier Reef, Australia. Three of them belong to the caridean shrimp family Alpheidae, viz. Athanas shawnsmithi n. sp., Athanas daviei n. sp., and Athanopsis saurus n. sp.; all three were collected from burrows of unknown hosts. The fourth species, Axianassa heardi n. sp. from the burrowing mud-shrimp family Axianassidae, is described based on a male holotype from Lizard Island and an additional female specimen from Moorea, Society Islands, French Polynesia. The presence of a toothed diaeresis on the uropodal exopod and a well-developed epipod on the second maxilliped in A. heardi n. sp. are new characters for the genus Axianassa.